Analysis of Drug Managementin Pharmaceutical Warehouse of Pematangsiantar City Health Office - H, Magdalena E; W, Wiryanto; U, Harahap (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: to analyze the management of drugs in 2018-2019 in the pharmaceutical warehouse of the Pematangsiantar City Health Office.Method: This research is a descriptive study with concurrent and retrospective data collection. The data obtained were analyzed using indicators and compared with literature standards. This research was conducted in January-March 2020.Results: The results showed that there were 9 indicators that did not meet the management standards for drug management, namely the accuracy of planning; percentage of planning deviations; frequency of procurement of drug items per year; percentage of essential drug procurement; percentage deviations in the amount of drugs distributed; percentage of expired drug; average time of drug emptiness; Inventory Turn Over Ratio (ITOR); the percentage of on time delivery of the LPLPO and 3 indicators that meet the standards, namely the compatibility of the drug items with the DOEN; percentage of dead drug stock; and compatibility of the number of real goods with stock.Conclusion: Drug management in the pharmaceutical warehouse of Pematangsiantar City Health Office, including; planning, procurement, distribution, storage, recording and reporting in the Pematangsiantar City Health Office have not fully met the indicator standards.